Menyongsong Lahirnya Kompetensi Multikultural - Anwar, Ahmad Khoirul; Toekio, Soegeng (KEMADHA, 2011)
World Arts is an inherent part of human life and the land to work out any sense would think in the form of objects. Visual arts emerged as an important part in the scope of material culture and continue to grow in line with the dynamics people. Therefore much art work produced by artists which capable of pouring creativity through various media and occurred in various areas,including in Indonesia.When we try to listen to cultural wealth of nations, both verbal and non verbal, either primary or secular , would look so rich source garapnya. In these cultural treasures, the source of work posted very pour , very diverse, even comes with a power generating common outside. There are charm and unique taste it bears, including the diversity of form is loaded with symbolism and value adhi. From several sources mentioned that the aspect of literacy work of art it is possible to maturation media-character or moral reason which was rejected on the mores (ie, on the basis of norms of behavior habits, customs).Since the socio-political atmosphere culminated into a situation that brings an update on various aspects of life, the existence of art seem slightly delayed echo nya.Dua three decades before the millennium, the existence of the art of singing was enough to inspire a lot of the hype. State-laden islands local culture, was rushed to reinvent its image in the middle of a worldwide cultural upheaval. This does not mean that whats been growing and developing is a deviation from the existing cultural roots. Many observers have even glanced at the art of cultural behaviors that tend to compromise on the aspirations of the people who heterogin and dynamics of the times.Similarly, brief exposure can I convey on this occasion, and as a reflection of all that appears also in the works of artists on display and deliver meaningful messages for you in coverage mengapresiasikannya as the impact the results of the artist / artists.